Urban Dockland - Zulkeflee, Farhana; Ab Sani, Jasasikin; Hj. Baharuddin, Zainul Mukrim (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
South Port Klang is previously known as Port Swettenham. It is a National Load Centre and being managed by the Port Klang Authorities (PKA) which handle all sort of developments in this area. It also has linkages with 600 ports across 10 countries. The location is very strategic as it is only 40km from Kuala Lumpur and become one of the main gateways into Malaysia. This area is very active with the load and unloading cargo and passengers every day. However, South Port Klang is still struggling with some issues such as lack of heritage value, lots of abandoned areas and flooding. As for that reasons, this design thesis have the goal to rejuvenate Port Klang as an useful Urban Dockland which does not only help in promoting trade and commerce activities but also creating a green corridor for the users as well as for surrounding environment. In order to achieve the goal of this design thesis, several objectives have been listed to guide the design thesis process such as to rejuvenate heritage value in this area as to highlight its unique identity, to revitalise abandoned area by transforming it to be green space for the benefits of users & environment and to provide green infrastructure in creating a sustainable and conducive living for this area. Thus, this study articulates the strategies for a proposal on South Port Klang derived from several methods which are direct observation, document analysis and direct interview on special person and public. As a result, a concept of “Antiquarian Fusion” has been implemented in this design proposal to achieve the objectives and giving a new breath by mixing urban and heritage value to this area. Therefore, there are some solutions formulated through landscape design to cater all the needs of this site as well as the needs for target users and also the environment.